Experimental-numerical comparative study of performance and cost-effectiveness of partially- and fully-cooled photovoltaic thermal systems - Yassine El Alami; Elhadi Baghaz; Rehena Nasrin; Fatima Chanaa; Rachid Bendaoud; Sanjeevikumar Padmanaban; Mohamed Louzazni (Case Studies in Thermal Engineering, 2025)
In this paper, an experimental and numerical analysis was carried out to evaluate and compare the energy and exergy performances of three solar systems: a photovoltaic system (PV-S) without cooling, a partially-cooled photovoltaic thermal system (PVT-S) and a fully-cooled PVT-S. In addition, a comparison of payback times between PVT-Ss was carried out. The impact of mass flow and different solar irradiation levels on the energy and exergy performance of the three systems was also examined. Numerical analysis was carried out using COMSOL Multiphysics® software, and the results obtained were validated by experimental data collected in outdoor conditions. The results show that the fully-cooled system offers the best performance. Under 600–1200 W/m2 irradiation, cell temperature rises by 29.14 °C for the uncooled PV-S, 19.82 °C for the partially-cooled PVT-S, and 7.04 °C for the fully-cooled PVT-S. Electrical efficiency (EEF) decreases by 1.98 %, 1.35 %, and 0.48 % respectively. Thermal exergy efficiency increases by 9.49 % for the partially-cooled system and 11.7 % for the fully-cooled system. Maximum thermal efficiency (TEF) reaches 60.72 % for the partially-cooled system and 77.89 % for the fully-cooled system. Increasing the mass flow rate (MFR) from 0.0167 to 0.05 kg/s improves EEF by 0.14 % and 0.33 %, and TEF by 22.72 % and 30.15 % respectively. Finally, the fully-cooled system reduces payback time by 3.86 years compared with the partially-cooled system.